Multi-material single-vat dual-wavelength DLP 4D printing of shape memory polymers - Kröger, Finn; Schulte, Lennard; Spiegel, Christoph A.; Vázquez-Martel, Clara; Blasco, Eva (Smart materials and structures, 2025)
Shape memory polymers are a fascinating class of responsive materials with potential in various fields, especially when combined with precise structuring by three-dimensional (3D) printing strategies such as digital light processing (DLP). However, such 3D printing techniques are usually limited to homogeneous single material four-dimensional (4D) structures restricting potential applicability. In this study we present a dual-wavelength multi-material DLP-based strategy for the fabrication of 4D multi-material structures with a spatial controllable shape memory effect from a single ink formulation. To achieve this, we designed an ink system, allowing generation of static as well as responsive parts depending on the applied curing wavelength with a high spatial control. Specifically, the multi-material ink formulations are composed of epoxide-based, (meth)acrylate-based monomers and a radical photoinitiator—providing appropriate selectivity of the polymerization mechanism. A germanium-based derivative has been selected as a suitable radical photoinitiator active in the blue wavelength regime (460 nm), enabling the exclusive formation of poly(meth)acrylate-based networks exhibiting shape memory properties. When printing with UV light (365 nm), simultaneous formation of epoxy and polymethacrylate networks results in a non-responsive material. Finally, by exploiting these capabilities, the fabrication of multi-material 4D structures with spatially controllable shape memory properties is successfully demonstrated.
Online veröffentlicht: 30. Dezember 2024
Gesehen am 27.08.2025